PENGARUH MOTIVASI DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP KINERJA PENDAMPING PROGRAM KELUARGA HARAPAN KEMENTRIAN SOSIAL KABUPATEN LAMPUNG TIMUR - Dwi Wijayanto (e-JKPP, 2016)
ABSTRACT Achievement of organizational goals is influenced by its employees. Employees should be given the motivation to work more diligently in order to produce a performance that is consistent with the objectives of the organization. Besides motivation, human resources plays a very important in an organization. For that I am keen to take the title Motivation Influence of Human Resources and Quality Companion Program Performance Against Family Hope Ministry of Social Affairs in East Lampung regency.This study aims to identify and explain 1) Effect of Motivation on Performance Companion Social Ministry of the Family Hope Program In East Lampung district ". 2) Effect of Human Resource Quality Companion Program Performance Against Family Hope Ministry of Social Affairs in East Lampung district ". 3) Motivation Influence of Human Resources and Quality Companion Program Performance Against Family Hope Ministry of Social Affairs in East Lampung regency. Methods of data collection in this study using observations, questionnaires and documentation. Data analysis techniques in this study using a qualitative analysis performed using the analysis tables while quantitative analysis is based on primary data obtained from questionnaires to the respondent, then the result of the respondents' answers are calculated by linear regression formula.Based on the research it is known that a significant effect Motivation Performance Against Companion Social Ministry of the Family Hope Program In East Lampung regency. Quality Human Resources Assistants have a significant effect on Performance of Social Ministry of the Family Hope Program In East Lampung regency. Motivation and Quality of Human Resources Assistants have a significant effect on Performance of Social Ministry of the Family Hope Program In East Lampung regency. The amount of influence motivation and quality of human resources to employee performance is 70.1%. The magnitude of these effects show that the contribution of motivation and the quality of human resources to employee performance is positive meaning that if the motivation and human resources be increased to better, it will improve the performance of staff and vice versa if a decreased motivation factors and human resources, there will be a decline in performance employees. Keywords: Motivation, Human Resources, employee performance.